Cephalometric Comparison of Two Old Anatolian Peoples With The Contemporary Others - İlter Uzel; Ali Gültan; Osman Bengi (Galenos Yayinevi, 1988)
Human being skeletons which have been obtained from Anatolia, the motherland of many historical civilizations, are obviously very valuable materials for both anthropologs and archeologs. In the meantime, the metric comparisons which are done by using lateral cephalograms taken in standard conditions for the purpose of analyzing maxillofacial is important not in only orthodontic but also in anthropology. In the research, lateral sefalograms of contemporary human being taken in standard conditions and human skulls belonging to antic civilizations located in two different part Anatolia were used. Tracings and measurements were made on these cephalometric radiographs. A comparison was made between the cephalometric values of these human skulls taken from Antic Urla in west Anatolia and Malatya Aslantepe in east Anatolia. And then, they were also compared biometrically with the caphalometric values of contemporary human being in order to discover the differences between their values of maxillofacial structure. Finally, the reasons of above mentioned differences if there is any, Were discussed and maxillofacial evolution of Anatolian people vas tried to be stated throughout history.